2018
DOI: 10.1371/journal.pone.0197517
|View full text |Cite
|
Sign up to set email alerts
|

RNA extraction from self-assembling peptide hydrogels to allow qPCR analysis of encapsulated cells

Abstract: Self-assembling peptide hydrogels offer a novel 3-dimensional platform for many applications in cell culture and tissue engineering but are not compatible with current methods of RNA isolation; owing to interactions between RNA and the biomaterial. This study investigates the use of two techniques based on two different basic extraction principles: solution-based extraction and direct solid-state binding of RNA respectively, to extract RNA from cells encapsulated in four β-sheet forming self-assembling peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
(36 reference statements)
2
12
0
Order By: Relevance
“…2. This finding broadly supports the work of other studies [26][27][28] linking natural polymers with positively charged amine groups with decreases in RNA yield or quality. Several possible explanations could describe these findings.…”
Section: Discussionsupporting
confidence: 90%
“…2. This finding broadly supports the work of other studies [26][27][28] linking natural polymers with positively charged amine groups with decreases in RNA yield or quality. Several possible explanations could describe these findings.…”
Section: Discussionsupporting
confidence: 90%
“…This reduction in the yield was probably due to the presence of fibrils. A study by Burgess et al, 2018 (9) undertook a comparative analysis of RNA extraction from cells encapsulated in self-assembling peptide hydrogels using two different extraction principles: solution-based extraction and direct solid-state binding of RNA and showed the latter was a more efficient method of extraction (9). In line with this study, we have shown that the use of a direct solid-state binding of RNA extraction method allowed the extraction of RNA of PeptiGel ® -organoids.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this study, we have shown that the use of a direct solid-state binding of RNA extraction method allowed the extraction of RNA of PeptiGel ® -organoids. Burgess et al, also showed that the use of pronase, a broad-spectrum enzyme solution reduced the amount of fibril present and increased RNA yield (9). Therefore, future investigation will aim to increase the yield of the RNA content by employing the use and impact of pronase to digest the organoids lysate before being subjected to RNA analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to avoid this is to use cells from different species, so that species-specific primers can be used for identifying transcript changes. Alternatively, cells can be extracted from the hydrogel and separated by flow cytometry, although enzymes used to digest the polymer network may degrade the cellular material to be measured or interfere in the subsequent detection [ 166 ]. Changes in junctional complex mRNA expression in brain endothelial cells generally correlate with the protein level changes and functional changes in TEER [ 167 ].…”
Section: Outcome Measurements Of Bbb Functionality In Nvu Modelsmentioning
confidence: 99%